Giant pyroelectric properties achieved at a wide temperature range in lead-free sodium bismuth titanate-based and composite ceramic materials. - Balakt, Ahmed Muwafaq J. (Cranfield University, 2017)
Health and environmental concerns have universally increased in importance during the last several decades. In the material science sphere, researchers are racing to replace poisonous, PZT-based pyroelectric materials with nonhazardous environmentally friendly ones, which simultaneously possess enhanced properties and provide the high performance. Beside environmental issues, the lower pyroelectric response and narrow operating temperature range have been identified as significant drawbacks of presently used lead-free pyroelectric materials for future diverse advanced industrial applications. One of the possible, most challenging and highly promising solutions to those industrial problems is utilizing composite ceramic materials (CCMS). Those materials combine the best raw materials properties and the sophisticated design. Therefore, they provided better performance compared to the original materials. The major aim of this systematic study is to investigate and improve the pyroelectric properties of lead-free sodium bismuth titanate modified by barium titanate ceramics, Na1/2Bi⅟₂TiO₃-0.06BaTiO₃ (NBT-0.06BT), at the morphotropic phase boundary (MPB) over a wide range of frequencies and temperatures. The secondary goal is to control and lower the first phase transition temperature, termed depolarisation temperature (Td), to around room temperature (RT). Three different techniques were used: (1) modifying the composition by altering A-site element contents; (2) doping the A- and/or B-sites with selective elements; and (3) forming composite pyroelectric ceramic material (CPCM). This study confirms that NBT-0.06BT at the MPB regains its critical composition and is sensitive to any compositional modification. These changes in NBT-0.06BT composition can shift its structure slightly away from the MPB area and will considerably change its pyroelectric properties. It was found that the pyroelectric properties at RT and Td were significantly enhanced by tailoring the NBT-0.06BT composition. Likewise, Td was controlled and decreased by implementing the same techniques as used to tailor the material composition. This study succeeded in increasing the range of the pyroelectric coefficient temperature response from one sharp peak at an exact temperature to a broad peak, which extends to around 25 °C with maximum pyroelectric coefficient (7.10 × 10⁻4 C.m⁻².°C⁻¹ at 40 °C) by developing CPCM. This significant achievement can expand considerably the range of the pyroelectric working temperature and is, therefore, both useful and valuable for a wide variety of pyroelectric applications.
Keywords: Electroceramic; Lead-free ceramics 0.94Na₀․₅Bi₀․₅TiO₃-0.06BaTiO; Morphotropic phase boundary (MPB); Modified A-site elements of NᵪByT- 0.06BzT; A or B site doped NBT-0.06BT; both sites doped NBT-0.06BT; Composite pyroelectric ceramic materials (CPCM); Depolarization temperature (Td); Figure of merits (FOMs); Pyroelectric properties